Spatial and Temporal Trends in PM2.5 Organic and Elemental Carbon across the United States - J. L. Hand; B. A. Schichtel; W. C. Malm; N. H. Frank (Advances in Meteorology)
The rural/remote IMPROVE network (Interagency Monitoring of Protected Visual Environments) and the Environmental Protection Agency's urban Chemical Speciation Network have measured PM2.5 organic (OC) and elemental carbon (EC) since 1989 and 2000, respectively. We aggregated OC and EC data from 2007 to 2010 at over 300 sites from both networks in order to characterize the spatial and seasonal patterns in rural and urban carbonaceous aerosols. The spatial extent of OC and EC was more regional in the eastern United States relative to more localized concentrations in the West. The highest urban impacts of OC and EC relative to background concentrations occurred in the West during fall and winter. Urban and rural carbonaceous aerosols experienced a large (although opposite) range in seasonality in the West compared to a much lower seasonal variability in the East. Long-term (1990–2010) trend analyses indicated a widespread decrease in rural TC (TC = OC + EC) across the country, with positive, though insignificant, trends in the summer and fall in the West. Short-term trends indicated that urban and rural TC concentrations have both decreased since 2000, with the strongest and more spatially homogeneous urban and rural trends in the West relative to the East.